A survey of the impact of agricultural legislation on common law principles with special reference to the following statutes - Giemre, William Rudolph (Centre for Law and Society, 2026)
The increasing complexities of modern life have led to the promulgation of more and more legislation each year. However necessary such legislation may appear to be to regulate our daily lives, it is not, by any means, an unmixed blessing. Much of this legislation impinges on our common law principles which have regulated man 1s conduct for centuries past.